Anne of Avonlea. #2 - Montgomery, L. M. (Lucy Maud), 1874-1942 (The Anne of Green Gables, 2014)
Anne has reached the age of sixteen, and begins teaching at the Avonlea school, but finds she still has much in common with her pupils.